ANALISIS KEMAMPUAN SISWA MENYELESAIKAN SOAL PISA DALAM KONTEN RUANG DAN BENTUK - Rezkiani, Putri; Warmi, Attin (IKIP Siliwangi, 2023)
This study aims to identify students' abilities in solving PISA questions in terms of space and form content. The research method used is qualitative with descriptive type. The research subjects were 3 students of class VII SMP in Karawang. The researcher used a research instrument in the form of a description test which was adopted from the PISA book Released Items – Mathematics which was translated into 2 questions. Researchers chose 3 subjects to be analyzed based on high, medium, and low categories. The results of the research that has been carried out from 39 students who completed PISA questions in space and form content, 4 students are in the high category with a percentage of 10.3%, 29 students are in the medium category with a percentage of 74.4%, and 6 students are in the low category with percentage 15.3%. Of the 39 students who completed PISA questions in spatial and shape content, almost half of the students tested were able to complete question 1, and fewer students were able to complete question 2 compared to students working on question 1